Delivery Outcome in Spontaneous and Induced Labour: A Prospective Comparative Study - Chosdon, Padma; Ladol, Chusnit (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
Induction of labour is the most common procedures during pregnancy1 .Labour induction is the artificial initiation of uterine contraction prior to their spontaneous onset by using cervical ripeners, leading to progressive dilatation and effacement of cervix and delivery of baby1. In this study I have compared delivery outcomes in spontaneous and induced labour. Although there are many drugs and forms available for induction of labour, this study uses vaginal misoprostol tablets for induction of labour. Tablet misoprostol is a prostaglandin analogue-specifically, a synthetic prostaglandin E1(PGE1) have been routinely used for induction of labour nowadays 2 .
Keywords: Apgar score; caesarean; delivery; induced; misoprostol; neonate; partograph; spontaneous; vaginal